THE EFFECT OF COOPERATIVE LEARNING STRATEGY ON STUDENTS’ SPEAKING ABILITY AT SMA MARDI LESTARI MEDAN - Renni Rosianna Lumbangaol (Journal MELT (Medium for English Language Teaching), 2018)
This study was intended to find out the effect of using cooperative learning strategy on students’ speaking ability of SMA Mardi Lestari. The research was conducted by quantitative research that used experimental group and control group. The population of this study was all the second year students of SMA Mardi Lestari Medan. 49 students were taken as the sample of this research. The sample was divided into two groups: the first group (25 students) as the experimental group and the second group (24 students) as the control group. The writer used t-test formula to analyze the data. The data were calculated by using t-test formula. The result of the analysis shows that t-observed (6.13) is higher than t-table (3.551) at the level of significance 0.01 and the degree of freedom (df) 47. Therefore, the null hypothesis (Ho) is rejected the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that Cooperative Learning Strategy affects the students’ speaking ability.